DEVELOPMENT AND POVERTY: A SYMBIOTIC RELATIONSHIP AND ITS IMPLICATION IN AFRICA - Oyeshola, Dokun (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Poverty is present everywhere but the kind in Africa is of great magnitude both in its spread and destitutive dimension. In other places any manifestation of poverty is a challenge to move forward but in Africa, the reverse is the case. Therefore the continent and international community are not happy about it, hence various programmes and strategies were put in place. Ironically there is little to show for it. For instance, about ten years before the end of millennium, the common slogan in Africa was ‘water for all, food for all, education for all, health for all and so on by the year 2000’. The ‘miracle’ year 2000 has come and gone and water, food, education and health are not enjoyed by many citizens of the continent. Development is still illusive. In this paper I examine the issues of poverty and development in the context of deforestation/biodiversity a consequent effect of global warming being one of the major threats to humanity. Some questions are raised with a view to proffer recommendations that may move the continent forward. These are: What are the roots of poverty in Africa? Why should there be a symbiotic relationship between poverty and development in Africa? Can Africa really develop?